Assessing the impact of online education on visually impaired students at the University of Limpopo : a development management perspective through the lens of social inclusion and digital learning - Soana, Modula Marcia (My University, 2025)
This study Assessed the Impact of Online Education on Visually Impaired Students at the University of Limpopo: A Development Management Perspective through the Lens of Social Inclusion and Digital Learning. The study seeks to understand and explore the effects of online teaching and learning experience of visually impaired students. The study also assessed the challenges that visually impaired students face during online teaching and learning. Opportunities to enable effective online teaching and learning for visually impaired students and recommendations measures that can be implemented to overcome online teaching and learning challenges for visually impaired students. This study employed a qualitative research approach, and interviews were used to collect data from the respondents. The respondents were fifteen visually impaired students and three Reakgona Disability Centre staff members. The aim of this research study is to investigate the effects of online learning on visual impaired students at the University of Limpopo, to investigate the accessibility of online learning for visually impaired students, to identify the barriers to effective online learning for visually impaired students, to identify opportunities to enable effective online learning for visually impaired students, and to recommend measures that can be implemented to overcome online learning challenges on visually impaired students. The main findings presented in this study are the demographics of the participants and key informants, online teaching and learning experiences of visually impaired students, assistive devices that are used by visually impaired students to access online classes, suitable study materials for visually impaired students, visually impaired students’ academic performance, preferred class attendance method/mode for visually impaired students and the challenges faced by visually impaired students when attending online classes.
Thesis (M. Dev. (Planning and Management)) -- University of Limpopo, 2025
Keywords: Online teaching and learning; Visually impaired; Disability; Assistive device; Accessibility; Web-based instruction; People with disabilities -- South Africa -- Limpopo Province; People with visual disabilities; Education, Higher -- South Africa -- Limpopo; Social integration; Students with visual disabilities